Bioassay of acaricide resistance on three common cattle tick species around Holetta area - Shiferaw, Y.; Girma, A.; Jobre, Y.; Hailemariam, M.; Zerbini, E. (Ethiopian Society of Animal Production, 1998)
Bioassay of acaricide resistance on three common cattle tick species was conducted at the Institute of Agricultural Research, Holetta Research Centre by using standardized FAO Acaricide Resistance Test Methods. Larval progeny of Boophilus decoloratus, Rhipicephalus evertsi evertsi and Amblyomma varigatum were subjected to larval packet test (LPT) employing four different acaricides namely, Dieldrin, Diazinon, Chlorefenvinphos and Coumpaphs, each with five concentration levels. Statistical assessment of pooled mortality rates (least square means (+ or -) standard error) to the tested acaricides were 67.93 (+ or -) 0.86 for B. decoloratus, 97.93 (+ or -) 0.86 for R. e.evertsi and 97.23 (+ or -) 0.86 for A. varigatum. These values were different (P<0.001) between B. decoloratus on the one hand and R. e.evertsi and A. varigatum on the other hand. However, there was no differences (P>0.05) between R. e. evertsi and A. varigatum. The efficacy of Dieldrin, Diazinon, Chlorefenvinphos and Coumaphos against all test ticks were 74.27 (+ or -) 0.99, 84.72 (+ or -) 0.99, 96.82 (+ or -) 0.99 and 94.98 (+ or -) 0.99, respectively. Dieldrin and Diazinon and Diazinon had higher (P<0.001) killing rates of test ticks than Chlorfenvinphos and Coumaphos. The finding of organophosphate (Diazinon) resistance is the first Report of its kind in the country. It is generally presumed that resistant tick population is emerging at an increasing pace in the area warranting a serious attention. The poor efficacy of Dieldrin and Diazinon may be attributed to the extensive use of chemicals like BHC & Bacdip. Furthermore, their faulty application characterized by irregular spraying, failure to maintain adequate lethal concentrations, reliance on one component of tick control strategy and other managerial constraints could have contributed to the developed resistance problems. It is therefore, high time to revise and consider the existing or other tick control strategies that could best address the alarming resistance problem as well as the managerial constraints hampering the successful use of acaricides.